Komunikasi Penanganan Konflik Tanah Ulayat di Kecamatan Batipuh Selatan Kabupaten Tanah Datar - Ningsih, Sri Wahyu; Asmawi, Asmawi; Chatra, Emeraldy (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This study aims to describe and analyze the dynamics of communication in handling Nagari Sumpur customary land conflicts, communication in conflict management of the Ulayat Land Team, and communication barriers faced by the Nagari Sumpur Ulayat Land Team, South Batipuh District. This research uses a qualitative approach with a case study method. As a reference in processing data, researchers use conflict management theory. The results showed that the dynamics of communication in handling customary land conflicts in Nagari Sumpur had political involvement in it. The local government that took office at that time seemed a bit reluctant for fear of reducing its political votes at the time of the election. In addition, the dynamics of communication in handling customary land conflicts in Nagari Sumpur continue to experience changes in patterns, content and channels. The dynamics of communication can also be seen from the emotional involvement of the communicating party. The Tanah Ulayat Team is in a moderate dynamic which means that the Tanah Ulayat Team communicates well in internal meetings with the team. High communication dynamics occur if external meetings that present all institutions, elements and society. As for conflict management, the Tanah Ulayat Team prioritizes the interests of Nagari by striving and striving so that the objectives in handling Nagari customary land conflicts can be resolved.